2002
DOI: 10.1017/s0022112001007674
|View full text |Cite
|
Sign up to set email alerts
|

The temporal evolution of neutral modes in the impulsively started flow through a circular pipe and their connection to the nonlinear stability of Hagen–Poiseuille flow

Abstract: The linear stability of the impulsively started flow through a pipe of circular crosssection is studied at high Reynolds number R. A crucial non-dimensional time of O(R 7/9 ) is identified at which the disturbance acquires internal flow characteristics. It is shown that even if the disturbance amplitude at this time is as small as O(R −22/27 ) the subsequent evolution of the perturbation is nonlinear, although it can still be followed analytically using a multiple-scales approach. The amplitude and wave speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 27 publications
(36 reference statements)
4
20
1
Order By: Relevance
“…For example, the linear stability of spatially-developing pipe and channel flows is governed by modes with an O(R) wavelength, comparable to the lengthscale over which the basic flow is developing (Smith and Bodonyi 1980). The corresponding neutral modes in temporally-developing pipe flow exhibit the same behaviour (Walton 2002). A further situation where the linearized version of (2.12) is relevant is the stability of the axial flow in a concentric annulus, where the equations describe the travelling-wave instability close to the cut-off in radius ratio or sliding velocity (Gittler 1993, Walton 2004.…”
Section: Formulation Of the Long Wave Interaction Equationsmentioning
confidence: 99%
“…For example, the linear stability of spatially-developing pipe and channel flows is governed by modes with an O(R) wavelength, comparable to the lengthscale over which the basic flow is developing (Smith and Bodonyi 1980). The corresponding neutral modes in temporally-developing pipe flow exhibit the same behaviour (Walton 2002). A further situation where the linearized version of (2.12) is relevant is the stability of the axial flow in a concentric annulus, where the equations describe the travelling-wave instability close to the cut-off in radius ratio or sliding velocity (Gittler 1993, Walton 2004.…”
Section: Formulation Of the Long Wave Interaction Equationsmentioning
confidence: 99%
“…Moreover, these asymptotic structures remain essentially intact as the disturbance size is increased, and so this high Reynolds number approach allows us to incorporate the effects of nonlinearity in a self-consistent manner. In Walton (2002) the mode structure on the upper branch of the weakly nonlinear neutral curve was analyzed at large Reynolds number for nonsymmetric disturbances proportional to exp(iN θ). There it was found that for N = 1 the asymptotic structure develops into the travelling-wave structure for HPF proposed by Smith & Bodonyi (1982), with the time dependence of the basic flow having a purely parametric effect on the nonlinear modes.…”
Section: The Governing Equations and Basic Flowmentioning
confidence: 99%
“…It is shown in Walton (2002) that, at least as far as nonsymmetric modes are concerned, curvature effects first enter the upper branch stability structure at viscous times of O(R −2/9 ) after the fluid is set into motion. This occurs because at this time, the radial velocity in the wall layer has grown to a sufficient size to balance the curvatureinduced phase shift from the critical layer.…”
Section: The Asymptotic Upper Branch Structure In the Linear Regimementioning
confidence: 99%
See 2 more Smart Citations